2022-RA-1120-ESGO Non-inferior survival outcomes from minimally invasive radical hysterectomy in conization-skipped, 2018 FIGO stage IB1 cervical cancer: A two-institutional retrospective cohort study. (20th October 2022) - Kim, Nae Ry; Lee, Seoyoon; Kim, Se Ik; Kim, Jae-Weon; Choi, Chel Hun; Lee, Maria
Abstract : Introduction/Background: Recently, we demonstrated that preoperative conization might reduce the disease recurrence in early cervical cancer patients who undergo primary radical hysterectomy (RH) by a minimally invasive surgical (MIS) approach. However, conization is not mandatory as per the current clinical practice guidelines. Thus, this study aimed to compare survival outcomes between MIS and open RH among patients who did not receive preoperative conization. Methodology: From cervical cancer cohorts of two institutions, we identified pathologically node-negative, margin-negative, parametria-negative, 2018 FIGO stage IB1-IB2 cervical cancer patients who received primary Type C RH between July 2006 and June 2020. Patients who received cervical conization before RH were excluded. The study population was divided into MIS (n=196) and open (n=156) groups. Patients' clinicopathologic characteristics and survival outcomes were compared between the two groups. Results: Between the MIS and open groups, no differences were observed in histologic type, cervical tumor size, and depth of invasion. After a median follow-up of 63.5 months, overall survival was similar between two groups; however, MIS group showed worse disease-free survival (DFS; 5-year rate, 79.4% vs. 91.1%; P=0.011). In multivariate analysis, MIS was identified as an independent poor prognostic factor for DFS (adjusted HR, 2.027; 95% CI, 1.1130–3.635; P=0.018). However, among IB1 patients (n=107), no difference in DFS was observed between the MIS and open groups: multivariate analysis revealed that MIS did not influence the disease recurrence rate (P=0.142). Conclusion: In conization-skipped, 2018 FIGO stage IB1 cervical cancer, MIS might not increase the disease recurrence rate after RH. Accurate preoperative identification of nodal and parametrial involvement is essential for early cervical cancer patients in deciding the surgical approach of RH.